Menopausal Symptom Severity, Family Support and Coffee Consumption as Determinants of Sleep Quality among Menopausal Women in Indonesia - Diyu, Ida Ayu Ningrat Pangruating; Agustini, Ni Komang Tri; Sagitarini, Putu Noviana; Kamaryati, Ni Putu (Chakra Brahmanda Lentera Institute, 2026)
Background: Menopause represents a critical transition in women’s lives during which poor sleep quality is commonly reported yet often overlooked. However, limited evidence exists regarding factors associated with sleep quality among menopausal women in Indonesia, particularly from a biopsychosocial perspective. Therefore, this study aimed to identify factors associated with sleep quality among menopausal women. Methods: This cross-sectional study, reported in accordance with the STROBE guidelines, included 277 women aged ≥40 years recruited from the service areas of community health centres (Puskesmas) in Denpasar, Indonesia, using convenience sampling. Women receiving hormone replacement therapy, using medications for menopausal symptom relief, or with a history of hysterectomy or oophorectomy were excluded. Data were collected through self-administered questionnaires, including the Menopause Rating Scale (MRS), Family Support Scale (FSS), and Pittsburgh Sleep Quality Index (PSQI), all of which demonstrated acceptable validity and reliability. Sleep quality was the dependent variable, while menopausal symptom severity, family support, coffee consumption, physical activity, employment status, menopausal status, and comorbid conditions were examined as independent variables. Data were analysed using descriptive statistics, chi-square tests, and multivariate logistic regression. Results: Nearly half of the women reported poor sleep quality (49.5%). Multivariate logistic regression analysis identified menopausal symptom severity, family support and coffee consumption as significant factors associated with sleep quality. Women with moderate-to-severe menopausal symptom severity had 7.42 times higher odds of poor sleep quality than those with none-to-mild symptoms (OR=7.42; 95%CI: 3.95–14.70; p<0.001. Women with low family support had 5.98 times the odds of poor sleep quality than those with adequate family support (OR=5.98; 95% CI: 3.21–11.14; p<0.001). In addition, women who consumed coffee had 3.35 times higher odds of poor sleep quality compared with non-consumers (OR=3.35; 95%CI:1.90–6.56; p<0.001). Conclusion: Menopausal symptom severity, family support and coffee consumption were significantly associated with sleep quality among menopausal women. These findings may underscore the importance of considering biological, behavioural, and social factors when assessing sleep-related concerns and developing supportive care strategies for menopausal women.